Outdoor Advertising in the 2012 Ukraine Parliamentary Election - Łukasik-Turecka, Agnieszka (The Copernicus Journal of Political Studies, 2018)
The so-called outdoor advertising played a crucial role in the 2012 parliamentary elections campaign in Ukraine. The parties preparing their advertising messages applied different types of such advertising. The classic image advertising was one of the most popular advertising forms and it contained such standard elements, as: the candidate’s photograph, his/her last name, the party’s name, the candidate’s number on the electoral list, or the election slogan. In case of less known candidates ID advertising was applied. This type of advertising was chosen among others by Udar party which had Witalij Kliczko on its posters recommending candidates for the representatives of his party. The individual formations advertised themselves both by presenting their achievements and electoral promises. This campaign was not free of negative advertising, including its comparative and comic forms. The 2012 Ukrainian parliamentary elections did not differ from any European parliamentary elections both in terms of the applied advertising forms and the richness of such forms. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762